Representation of Indonesian Women Political Figures in Online Media during the 2014 and 2024 Elections: A Critical Discourse Analysis - Rizky Tazkiyatul Ummami; Ratna Juwitasari Emha; Abdul Aziz (Institut Pariwisata dan Bisnis Internasional, 2026)
This study examines how Indonesian women political figures are represented in online news media during the 2014 and 2024 general elections and identifies the discursive strategies used to construct their political identities across the two periods. Grounded in Fairclough’s (1995, 2010) three-dimensional model of Critical Discourse Analysis and complemented by van Leeuwen’s (2008) social actor representation framework, this qualitative diachronic study analyzes purposively selected news excerpts from Kompas.com, Detik.com, and Tempo.co that feature three prominent figures, Puan Maharani, Tri Rismaharini, and Khofifah Indar Parawansa. Data were manually coded at the textual, discursive, and social-practice levels and compared thematically across the two election years. The findings show that women political figures are represented through four dominant identities – political leader, professional politician, moral figure, and gendered public figure – constructed through five discursive strategies: conflict, performance, gender-based, moral-religious, and achievement framing. While performance- and achievement-oriented framing became more visible over the decade, traces of gender-based representation persisted, indicating an ongoing negotiation between professional political identity and patriarchal cultural expectations. The study concludes that Indonesian online media continue to shape political legitimacy through lexical, transitivity, and framing choices that are simultaneously progressive and gendered, and recommends broader comparative and multimodal research. Practically, the study offers online news media, gender-advocacy organizations, and political communication practitioners a concrete diachronic benchmark for auditing how women political figures are framed, informing more balanced, gender-sensitive reporting guidelines.